2019
DOI: 10.1038/s41437-019-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetic analyses of Cervus elaphus and Sus scrofa: comparative study and analytical developments

Abstract: Red deer and wild boar are two major game species whose populations are managed and live in areas impacted by human activities. Measuring and understanding the impact of landscape features on individual movements and spatial patterns of genetic variability in these species is thus of importance for managers. A large number of individuals sampled across Wallonia (Belgium) for both species have been genotyped using microsatellite markers (respectively > 1700 and > 1200 genotyped individuals) and some individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…With the absence of detected crossing motorway events, even for individuals having their home range immediately next to a motorway, the GPS data further confirmed the significant impact of motorways on the dispersal frequency of these individuals, which was previously demonstrated with capture-mark-recapture data (Dellicour et al, 2019). The analysis of GPS movement data also revealed that on average, individuals spent ~74% of their time in forest areas, with ~59% of them spending at least 75% of their time in forest areas (Figure 1).…”
Section: Preliminary Analyses Of Wild Boar Movement Datasupporting
confidence: 79%
See 1 more Smart Citation
“…With the absence of detected crossing motorway events, even for individuals having their home range immediately next to a motorway, the GPS data further confirmed the significant impact of motorways on the dispersal frequency of these individuals, which was previously demonstrated with capture-mark-recapture data (Dellicour et al, 2019). The analysis of GPS movement data also revealed that on average, individuals spent ~74% of their time in forest areas, with ~59% of them spending at least 75% of their time in forest areas (Figure 1).…”
Section: Preliminary Analyses Of Wild Boar Movement Datasupporting
confidence: 79%
“…Because the motorway segment is an apparent effective barrier to ASF and wild boar dispersal, which is also confirmed by the analysis of individual capture-mark-recapture (Dellicour et al, 2019) and GPS data, the forest raster was preliminary modified to assign a very low conductance value (1/[1,000 × k]) to raster cells crossed by the motorway segment.…”
Section: Investigating the Impact Of Ecological Factors On The Wavementioning
confidence: 97%
“…The null raster is a uniform raster with all cell values equal to 1. As in Dellicour et al (2019), three values of k (10, 100 and 1000) were used to modify the potential impact of the environment on the resistance/conductance value. We used multiple regressions on distance matrices (MRDM) coupled with commonality analyses (CA; [76]) to identify unique and common contributions of predictors to the variance in the environmental distance (response variable).…”
Section: Impact Of Environmental Factors On Genetic Differentiationmentioning
confidence: 99%
“…In addition, we also performed univariate analyses by comparing (i) the determination coe cient R² obtained from the linear regression of genetic distances on distances computed on the environmental raster and (ii) the determination coe cient R² obtained from the linear regression of genetic distances on distances computed on the null raster. Only the environmental factors associated with a R² higher than that the one obtained from the linear regression based on environmental distances computed on the null raster were selected for the multivariate analyses (MRDM-CA) [78]. The same criterions to identify a suppressors were used for the multivariate analysis as in the commonality analyses descriptions [79,80].…”
Section: Impact Of Environmental Factors On Genetic Differentiationmentioning
confidence: 99%
“…The proportion of shared alleles, D PS , (Draheim, Moore, Fortin, & Scribner, 2018; E. L. Landguth, Cushman, Murphy, & Luikart, 2010; Trumbo, Spear, Baumsteiger, & Storfer, 2013) and other kinship- or relatedness-coefficients (Dellicour et al, 2019; Renner et al, 2016) are popular choices and continue to be implemented in new applications developed for landscape genetic analyses (Savary et al 2020). However, many of these estimators have a large sample variance, which has recently been shown to negatively impact landscape genetic inferences (Winiarski, Peterman, & McGarigal, 2020).…”
Section: Introductionmentioning
confidence: 99%